MEDICINAL LEECH FOR THE TREATMENT OF ACNE VULGARIS W.S.R. TO MUKHADUSHIKA: A RANDOMISED CLINICAL STUDY - Gupta Sudesh; Sharma Sakshi; Prasher Aarushi; Sharma Kumar Arun; Manhas Raman (AYUSHDHARA, 2021)
Acne vulgaris is a chronic inflammatory disorder of the pilo-sebaceous follicles characterised by comedones, papules, pustules, nodules and often scars mainly seen on cheeks, chin, nose, forehead and upper trunk during adolescence. The symptoms of Acne vulgaris resemble Mukhadushika as per Ayurvedic classics. Acharya Sushruta has mentioned Mukhadushika as one of the Kshudra Rogas. In Mukhadushika, there are Shalmali kantak like eruptions on the face which are impregnated with Meda caused due to vitiation of Kaphadosha, Vatadosha and Raktadhatu which destroy the beauty of the face and makes the appearance ugly. The disease almost take place in adolescent and young age group prominently therefore is also known as Yuvanapidika. Acharya Sushruta stated Jalaukavacharana is the preferred method of bloodletting in Sukumara. Aim: To evaluate the efficacy of Jalaukavacharana in the management of Acne vulgaris w.s.r. to Mukhadushika. Methodology: Fourteen patients of age group 15-30 years having signs and symptoms of Mukhadushika were selected and four sittings of Jalaukavacharana on a seven day interval were given. Apart from treatment duration of 28 days, a follow-up was also done after 30 days. Results: Intervention was found to be highly significant (p<0.001) in Vedana, Kandu, Daha, number of Pidika, size of Pidika, Pidika ghanata, Shotha, Vaivarnyata. However, significant effect (p<0.05) was found in Vranavastu and non-significant result (p>0.05) was found in Srava. Conclusion: The results are satisfactory. Jalaukavacharana is proved to be an effective, time saving, affordable and acceptable treatment in Mukhadushika without causing any adverse effect.